أثر استخدام أنموذج وودز فى تحصيل طلاب الصف الخامس العلمى فى مادة الفيزياء وتنمية تفكيرهم الناقد - أمين، أحمد جوهر محمد; مصطفى، رضوان محمد (جامعة الموصل - كلية التربية الأساسية, 2011)
هدف البحث إلى معرفة أثر استخدام أنموذج وودز في تحصيل طلاب الصف الخامس العلمي في مادة الفيزياء. \ وللوصول إلى هذا الهدف تم صياغة فرضيتين صفريتين. وللتحقق من هاتين الفرضيتين تم اختيار عينة من طلاب الصف الخامس العلمي في الإعدادية المركزية للبنين وبلغ مجموع أفرادها (٧١) طالباً ، وتوزعت هذه العينة إلى مجموعتين إحداهما تمثل المجموعة التجريبية والأخرى تمثل المجموعة الضابطة وبواقع (٣٥ ، ٣٦) طالباً على التوالي ، وأجريت عملية التكافؤ على مجموعتي البحث في متغيرات (الذكاء، تحصيل مادة الفيزياء للسنة السابقة ، العمر الزمني ، التفكير الناقد) . \ وقد تم تدريس المجموعة التجريبية وفقاً لأنموذج وودز والمجموعة الضابطة وفقاً للطريقة الإعتيادية. \ وتطلب البحث وجود أداتين: الأولى إختبار تحصيلي في مادة الفيزياء وتكون بصيغته النهائية من (٤٥) فقرة إختبارية موضوعية من نوع المزاوجة (المطابقة) والاختيار من متعدد والتكميل (ملء الفراغات) . أما الأداة الثانية فهي إختبار التفكير الناقد وتكون بصيغته النهائية من (٧٥) فقرة إختبارية موزعة على (٥) مجالات لقياس القدرات العقلية الناقدة ممثلة بقدرات (الاستنتاج، تقويم الحجج ، معرفة الافتراضات ، الاستنباط ، التفسير) . \ وبعد جمع البيانات وتحليلها إحصائياً أظهرت النتائج ما يأتي : \ 1-\ يوجـد فـرق ذو دلالـة إحصـائية بـين مجمـوعتي البحـث فـي تحصـيل مـادة الفيزيـاء ولصـالح المجموعة التجريبية . \ 2-\ يوجـد فـرق ذو دلالـة إحصـائية بـين مجمـوعتي البحـث فـي تنميـة التفكيـر الناقـد ولصـالح المجموعة التجريبية . The study aimed at knowing the effect of using Woods’ model on the achievement of fifth scientific grade students in physics and developing their critical thinking . \ To achieve this objective , two null hypotheses have been formed . And to examine the validity of the two hypotheses , a sample of (71) students has been chosen from the scientific fifth grade in Al-Markazya secondary school for boys. The sample is divided into two groups the first one is the experimental group and the second one is the control group consisting of (35 – 36) students respectively. The two groups have undergone to equivalence process in variables of (intelligence, achievement of physics during last year, the age and the critical thinking). \ The experimental group has been taught according to Woods’ Model and the control group in the traditional method . \ The study required two tools, the first one is represented in an acquisitive test in physics, consisting of (45) objective test items of matching type and multiple choices to fill blanks. The second tool is the critical thinking test, consists which of (75) testing items distributed into (5) fields of testing the critical thinking abilities represented in the skills of (concluding, assessing evidence, knowing the hypotheses, deduction and interpretation) . \ Collecting and statistically analyzing the data , the two researchers have reached the following results: \ 1.\ There is a statistical difference between the two groups of the study in achievement of physics for the sake of the experimental group . \ 2.\ There is a statistical difference between the two groups of the study in developing critical thinking for the sake of the experimental group .
807536 699785 765955
Keywords: التحصيل الدراسى -- التعليم الثانوى -- طلاب المدارس الثانوية -- تدريس الفيزياء -- طرق التدريس -- السياسة التعليمية -- تنمية المهارات -- التفكير الناقد